THE PRACTICE AND VISION OF CONSCIENCE CULTURE: A GLOBAL CIVILIZATIONAL OPPORTUNITY THROUGH MULTILATERAL COLLABORATION (Religious dialogue and cooperation, 2025)
In today’s era of rapid globalization and change, humanity enjoys unprecedented convenienceand connectivity, yet faces value conflicts, social injustice, and cultural homogenizationthat threaten global peace and coexistence. Confronted with this global moral crisis, ConscienceCulture is emerging as a vital pathway for building consensus and restoring a shared ethical andvalue-based foundation. As a universal value that transcends religions, cultures, and ideologies,conscience serves not only as an inner moral compass for individuals but also as a crucial driver ofpractical action, international cooperation, and mutual trust. This paper draws on the Ti-Yong (Essence-Function) concept of Tai Ji Yin-Yang Philosophy, positioning conscience as the core essence(體, ti) of culture and morality, while its external expression (用, yong) is realized through moralintuition (良知, liangzhi) and moral capability (良能, liangneng). Together, these guide individualaction and institutional design, achieving an organic integration of inner awareness and the practiceof justice. Using Tai Ji Men’s global conscience and peace initiatives as examples, this paperdemonstrates how the cultural resilience of Conscience Culture—flexible yet firmly rooted—canhelp resolve the tensions and challenges posed by contemporary globalization. It further showshow Conscience Culture can guide humanity toward peace, fairness, and the moral renewal of humankind,opening new horizons for “global civilization.”
Keywords: Conscience Culture; Ti-Yong Philosophy; Moral Intuition; Cultural Resilience; Global Civilization